Indole Inhibits IncP-1 Conjugation System Mainly Through Promoting korA and korB Expression - Xiong, Rui; Liu, Yuyang; Pu, Jieying; Liu, Jianping; Zheng, Dexiang; Zeng, Jianming; Chen, Cha; Lu, Yang; Huang, Bin (Frontiers in Microbiology, 2021)
Indoles work as interspecies signal molecule to regulate multiple physiological activities, like antibiotic resistance, acid resistance and virulence. However, the effect of indoles on conjugation is unknown. Here, with Escherichia coli SM10λπ which is integrated with RP4 plasmid chromosomally as donor strain, we explored indoles’ function in conjugational transfer of a mobilizable antibiotic resistance plasmid. The results showed that exogenous indoles treatment or interference of endogenous indoles production both negatively regulated conjugation efficiency in two conjugational models SM10λπ-PAO1 and SM10λπ-EC600. Subsequent mechanistic studies revealed that exogenous indoles significantly promoted expression of korA and korB, which was also observed in strains of enhanced endogenous indoles production. Additionally, ciprofloxacin was introduced to study the effects on conjugation and indoles. We found 1/8 minimum inhibitory concentration of ciprofloxacin treatment obviously facilitated the ability of SM10λπ to conjugate with PAO1 or EC600, accompanied with decreased tnaA expression and indoles production. These data suggest that indoles play a role in the process of ciprofloxacin induced conjugation. Collectively, it is the first time to reveal the biological function of indoles inhibiting conjugation, which may be developed into a new way to control the spread of antibiotic resistance.